2005
DOI: 10.1007/s11373-005-6796-0
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Ca2+ signaling in tachykinin-mediated contractile responses in swine trachea

Abstract: Neuropeptide tachykinins, present within sensory nerves, have been implicated as neurotransmitters involved in nonadrenergic and noncholinergic airway muscle contraction. The signal transduction pathways of tachykinins on muscle contraction and Ca2+ mobilization were investigated in swine trachea. Tachykinins, substance P (SP) and neurokinin A (NKA), concentration (1 nM to 1 microM)-dependently induced contractile responses with removal of epithelium, whereas neurokinin B (NKB) did not alter the muscle tension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…In the present study, NKRselective agonist-induced [Ca 2ϩ ] i increases were partially blocked by verapamil. Likewise, Lin et al (28) reported that substance P-evoked airway smooth muscle contraction and transient Ca 2ϩ mobilization were partially inhibited by verapamil, indicating that the NKR-mediated [Ca 2ϩ ] i increases are associated with activation of voltage-gated Ca 2ϩ channels. They further demonstrated that smooth muscle contraction and [Ca 2ϩ ] i increases activated by substance P were also partially blocked under Ca 2ϩ -free external conditions (28).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the present study, NKRselective agonist-induced [Ca 2ϩ ] i increases were partially blocked by verapamil. Likewise, Lin et al (28) reported that substance P-evoked airway smooth muscle contraction and transient Ca 2ϩ mobilization were partially inhibited by verapamil, indicating that the NKR-mediated [Ca 2ϩ ] i increases are associated with activation of voltage-gated Ca 2ϩ channels. They further demonstrated that smooth muscle contraction and [Ca 2ϩ ] i increases activated by substance P were also partially blocked under Ca 2ϩ -free external conditions (28).…”
Section: Discussionmentioning
confidence: 95%
“…Likewise, Lin et al (28) reported that substance P-evoked airway smooth muscle contraction and transient Ca 2ϩ mobilization were partially inhibited by verapamil, indicating that the NKR-mediated [Ca 2ϩ ] i increases are associated with activation of voltage-gated Ca 2ϩ channels. They further demonstrated that smooth muscle contraction and [Ca 2ϩ ] i increases activated by substance P were also partially blocked under Ca 2ϩ -free external conditions (28). Together, these findings indicate that Ca 2ϩ influx from the extracellular space is a component of the transient initial phase of NKR-mediated transient [Ca 2ϩ ] i increases.…”
Section: Discussionmentioning
confidence: 95%
“…Activation of 5-HT 3 -receptor (5-HT 3 R) is known to increase cytoplasmic Ca 2+ levels via extracellular influx through L-type-and 5-HT 3 R Ca 2+ -permeable channels (Hargreaves et al, 1996;Homma et al, 2006;Ronde and Nichols, 1997;Takenouchi and Munekata, 1998). Additional evidence indicate that Ca 2+ influx is also linked to activation of other emetogenic receptors including SP tachykinin NK 1 (Lallemend et al, 2003;Lin et al, 2005;Miyano et al, 2010;Suzuki et al, 2010), dopamine D 2 (Aman et al, 2007;Wu et al, 2006), cholinergic M 1 (Oliveir and Correia-de-Sa, 2005;Sculptoreano et al, 2001), and histaminergic H 1 (Barajas et al, 2008) receptors. Moreover, other emetogens such as prostaglandins (Almirza et al, 2012;Rodríguez-Lagunas et al, 2010), cisplatin (Günes et al, 2009;Splettstoesser et al, 2007), rotavirus NSP4 protein (Hagbom et al, 2012;Hyser et al, 2010) and bacterial toxins (Poppoff and Poulain, 2010;Timar Peregrin et al, 1999) have the ability to induce extracellular Ca 2+ influx through Ca 2+ channels present in the cell membrane.…”
Section: Introductionmentioning
confidence: 99%
“…NK 1 R stimulation by substance P or corresponding selective agonists such as GR73632, can increase cytosolic Ca 2+ concentration. In fact GR73632-induced activation of NK 1 Rs can evoke intracellular Ca 2+ release from the sarco/ endoplasmic reticulum stores via Gα/q-mediated phospholipase C pathway, which subsequently evokes extracellular Ca 2+ influx through L-type Ca 2+ channels (LTCCs) [17][18][19]. The serotonergic 5-HT 3 receptor (5-HT 3 R) is a Ca 2+ -permeable ligand-gated ion channel [20].…”
Section: Emerging Roles Of Ca 2+ In Emesis 21 Emetic Receptor Stimumentioning
confidence: 99%